Complete mitochondrial genome of the Nigeria-Cameroon chimpanzee, Pan troglodytes ellioti (Primates: Hominidae). (3rd May 2016) - Wang, Bao-Hua; Wang, Yin-Hua; Tang, Ming-Gui; Chai, Hai-Xia; Xuan, Xing-Wei; Guo, Wei-Yan; Yang, Mu; Pu, Jian-Yi
Abstract: Chimpanzees are especially suited to teach us about ourselves, both in terms of their similarities and differences with human, and such important similarities and differences have also been noted for the incidence and severity of several major human diseases. In the present work, we report the entire mitochondrial genome of the Nigeria-Cameroon chimpanzee ( Pan troglodytes ellioti ) for the first time. Results shows that this mitogenome is 16, 559 bp long and consists of 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and 1 putative non-coding region (D-loop region). The genomic organization and gene order are the same as other Chimpanzees. The whole nucleotide base composition is 31.1% of A, 30.7% of C, 12.9% G, and 25.3% T, with a slight A+T bias of 56.4%. Most of the genes are encoded on H-strand, except for the ND6 subunit gene and 8 tRNA genes. The complete mitochondrial genome sequence reported here provides useful genetic information for P. t. ellioti, and will further contribute to the comparative genomics studies in primates.